A completive research on the feasibility and adaptation of shared transportation in mega-cities – A case study in Beijing. (15th November 2018) - Sun, Lishan; Wang, Shunchao; Liu, Shuli; Yao, Liya; Luo, Wei; Shukla, Ashish
Highlights: Shared transportation mitigates traffic and environmental pressures. Shared transportation is a supplementary way for public transportation. Shared transportation is gradually affecting the passengers' travel behavior. Credit management helps to improve shared transportation services. Abstract: Electric vehicle sharing (EVS) and bike sharing have been recognized as promising solutions to growingly serious problems of traffic congestion, air pollution, and insufficient parking spaces. This paper, based on the current research status, analyzes and evaluates the effect of shared transportation on alleviating or solving the traffic and environmental issues of mega-cities from five perspectives-resource, environment, convenience, economy and governance. Then, taking Beijing as a case, one of the representative giant cities, this paper investigates and analyzes the development situation, feasibility, and adaptation of shared transportation. Compared with 2015, the share of cars decreased by more than 3.2%, and the trip frequency decreased by more than 55% for private car owners in 2016. Shared transportation reduced energy consumption, nitrogen emissions and PM 2.5 by 45 million liters of gasoline, 540, 000 tons and 4.5 billion mg just in one year in Beijing in 2016. The results indicate that shared transportation has an important role and potential in alleviating traffic and environmental issues of mega-cities. A series of development suggestions and some practical considerations are provided at the end, which might supply good decision-making guidance for policy makers.